Helmet-Noninvasive Ventilation for Hospitalized Critically Ill COVID-19 Patients: Has Vaccination and the New Variants Changed Evidence? - Neves, Hugo (2022)
Noninvasive ventilation (NIV) is a technique for breathing support that significantly improves gas exchange and vital signs, reducing intubation and mortality rates. Helmets, unlike facemasks, allow for longer-term treatment and better ventilation, also being more cost-effective. As of today, we have found no reviews addressing this topic. This review aims to identify, map, and describe the characteristics of the use of noninvasive ventilation through helmet interface in critically ill COVID-19 adult patients hospitalized in acute care settings throughout the multiple moments that defined the COVID-19 pandemic. This scoping review will follow the methodology for scoping reviews proposed by JBI. A set of relevant electronic databases will be searched using terms such as COVID-19, helmet, and noninvasive ventilation. Two reviewers will independently perform the study selection regarding their eligibility. Data extraction will be accomplished using a researcher’s developed tool considering the review questions. Findings will be presented in tables and a narrative description that aligns with the review’s objective. This scoping review will consider any quantitative, qualitative, mixed-methods studies and systematic review designs for inclusion, focusing on the use of helmet on critically ill adult patients with COVID-19 hospitalized in acute care settings.